Trends and thematic directions culturally responsive teaching on students’ writing skills in multicultural classrooms: A systematic literature review - Chaesar, Ari Suryawati Secio; Andayani; Suhita, Raheni (Proceedings of International Conference on Research in Education, 2025)
This study presents a systematic review of the development of Culturally Responsive Teaching (CRT) in the teaching of writing skills within multicultural classrooms. The review aims to identify patterns in research development, map publication trends and thematic distributions, and interpret the theoretical and practical implications of existing findings to propose future research directions. The review procedure follows PRISMA guidelines, using Scopus-indexed publications up to 31 October 2025 as the primary data source, complemented by bibliometric analysis conducted with VOSviewer to reveal the intellectual structure and dynamics of the field. The findings indicate that research on CRT in writing instruction predominantly addresses the integration of students’ linguistic and cultural backgrounds, identity reinforcement, and inclusive instructional design. The theoretical insights confirm CRT’s contribution to enhancing instructional relevance and students’ critical awareness, while practical implications are reflected in increased student engagement and improved writing performance. Identified research gaps highlight the need for conceptual studies in developing-country contexts, longitudinal examinations, and the development of adaptive CRT pedagogical models aligned with technological advancements.